Implementasi Program Pengabdian Masyarakat melalui KKN Kolaboratif 201 dalam Upaya Pencegahan dan Penanganan Stunting di Desa Gunungmalang, Kecamatan Sumberjambe, Kabupaten Jember - Fauziyah Almas Janani Widodo; Imelda Febbynatasya; Reni Kusumah Wardani; Devita Sari; Dewi Suryandini; Eka Putri Dewi (Jurnal Pengabdian Bidang Kesehatan, 2025)
Stunting is a chronic nutritional problem that impacts the physical growth and cognitive development of children, one of the causes is inappropriate parenting patterns such as exclusive breastfeeding, diet, and lack of nutritional fulfillment so that children are at risk of malnutrition. In Jember Regency itself, the high rate of stunting is a serious challenge for the government and the community that needs to be addressed. The selection of Gunungmalang Village as the location of community service is based on the high rate of stunting and early marriage as one of the causes of stunting. This community service activity began with training for Family Support Team (TPK) and Posyandu cadres, outreach to pregnant women, parents of infants/toddlers regarding the prevention and treatment of stunting, and a cooking demonstration of vegetable nuggets as an output of the activity by utilizing food ingredients that are easily available in the Gunungmalang community as an initial step to fulfill the nutrition of toddlers. This study uses a descriptive qualitative approach as a method from a case study of scientific paper research that describes factually and in detail related to the activities of the CINTA (Prevent Stunting and Increase Nutrition) work program. The objective of this scientific study is to implement a community service program through collaborative Community Service Programs (KKN) to prevent and address stunting in Gunungmalang Village. Data collection techniques used triangulation (observation, interviews, and documentation). This study demonstrates that the implementation of the community service program has a positive impact on increasing community awareness and changing behavior regarding stunting